An observational study of the safety benefits of electronic logging devices using carrier-collected data. (3rd April 2017) - Hickman, Jeffrey S.; Guo, Feng; Camden, Matthew C.; Dunn, Naomi J.; Hanowski, Richard J.
ABSTRACT: Objective : Fatigue has been shown to be a contributing factor in many large truck crashes. Long duty periods, irregular work schedules, and poor sleeping environments make fatigue a noteworthy concern in trucking operations. One way to limit fatigued driving is through prescriptive hours-of-service (HOS) regulations. This duty status information is typically recorded in written logs; however, more trucking companies are moving toward electronic HOS recorders. These devices were first marketed as productivity tools; however, more recently they have been touted for their safety benefits in reducing fatigued truck drivers (because falsifying electronic logs is difficult). Methods : The purpose of the current study was to assess the benefits of electronic logging devices (ELDs) on safety and HOS violations in trucks as they operated during normal revenue service. Data on crashes, HOS violations, mileage, and onboard safety systems were obtained from participating motor carriers. Although the final data sets included data from 11 carriers representing medium and large carriers (including a total of 82, 943 crashes, 970 HOS violations, and 224, 034 truck-years that drove a total of 15.6 billion miles), the data set in the study was skewed toward larger, for-hire carriers and may not represent the overall U.S. trucking population. Results : After controlling for calendar year, carriers in the data set, onboard safety system status, and long-haul/regional indicator, ELD-equipped trucks had a significantly lower total crash rate (11.7% reduction), preventable crash rate (5.1% reduction), driving-related HOS violation rate (53% reduction), and non-driving-related HOS violation rate (49% reduction) than trucks not equipped with ELDs. Conclusion : The results show a clear safety benefit, in terms of crash and HOS violation reductions, for trucks equipped with ELDs.